Nanofiltration of growth media supplemented with human platelet lysates for pathogen-safe xeno-free expansion of mesenchymal stromal cells - Barro, Lassina (Cytotherapy, 2020)
BACKGROUND AIMS: Human platelet lysate can replace fetal bovine serum (FBS) for xeno-free ex vivo expansion of mesenchymal stromal cells (MSCs), but pooling of platelet concentrates (PCs) increases risks of pathogen transmission. We evaluated the feasibility of performing nanofiltration of platelet lysates and determined the impact on expansion of bone marrow–derived MSCs. METHODS: Platelet lysates were prepared by freeze-thawing of pathogen-reduced (Intercept) PCs suspended in 65% storage solution (SPP+) and 35% plasma, and by serum-conversion of PCs suspended in 100% plasma. Lysates were added to the MSC growth media at 10% (v/v), filtered and subjected to cascade nanofiltration on 35- and 19-nm Planova filters. Media supplemented with 10% starting platelet lysates or FBS were used as the controls. Impacts of nanofiltration on the growth media composition, removal of platelet extracellular vesicles (PEVs) and MSC expansion were evaluated. RESULTS: Nanofiltration did not detrimentally affect contents of total protein and growth factors or the biochemical composition. The clearance factor of PEVs was >3 log values. Expansion, proliferation, membrane markers, differentiation potential and immunosuppressive properties of cells in nanofiltered media were consistently better than those expanded in FBS-supplemented media. Compared with FBS, chondrogenesis and osteogenesis genes were expressed more in nanofiltered media, and there were fewer senescent cells over six passages. CONCLUSIONS: Nanofiltration of growth media supplemented with two types of platelet lysates, including one prepared from pathogen-reduced PCs, is technically feasible. These data support the possibility of developing pathogen-reduced xeno-free growth media for clinical-grade propagation of human cells.